Advanced polymer composites for structural applications in construction proceedings of the second international conference, held at the University of Surrrey, Guildford, UK on 20-22 April 2004 - Hollaway, L. (Leonard); Chryssanthopoulos, M. K.; Moy, Stuart S. J. (Woodhead Pub., 2004)
Over the past three decades advanced polymer composites have emerged as an attractive construction material for new structures and the strengthening/rehabilitation of existing buildings and bridges. The techniques associated with the technology, analysis and design of polymer composites in construction are continually being researched and the progress made with this exciting material will continue at an ever- increasing rate to meet the demands of the construction industry. This volume of proceedings is from the Second ACIC 2004 International Conference, which focused on the application and further exploitation of advanced composites in construction. The conference allowed practising engineers, asset managers, researchers and representative of regulatory bodies to promote the active exchange of scientific and technical information on the rapidly changing scene of advanced composites in construction. This volume focuses on the presentation of new concepts, techniques and case studies, which will lead to greater exploitation of advanced polymer composites and FRP materials for civil engineering infrastructure, rehabilitation and renewal. Presents new concepts, techniques and case studies.